Parents’ Beliefs About Play and the Purpose of Preschool Education, Preschoolers’ Home Activity and Executive Functions - Metaferia, Biruk K.; Futo, Judit; Drew, Raechel; Takacs, Zsofia K. (Frontiers in Psychology, 2020)
The purpose of the present study was to replicate and extend previous findings that depict a link between preschoolers’ home experience and EFs. It also examined Hungarian parents’ views about the purpose of preschool education and its relationship with their play beliefs. A total of 87 Hungarian preschoolers participated in neuropsychological testing of executive functioning (44 boys, 42 girls, one not reported; mean age = 62.37 months; SD = 8.33 months; age range = 47 – 80 months) and their parents (eight male and 79 females; mean age = 37.73 years; SD = 5.64 years; age range = 22 – 63 years) filled in questionnaires. The finding from hierarchical regression analyses depicted that the frequency of pretend play the preschoolers engage in and parental play support beliefs were small to medium-sized predictors of children’s inhibitory control, after accounting for age and SES. Children’s frequency of participation in fine motor activities at home was a small but significant predictor of their visual-spatial working memory, after controlling for age and SES. Furthermore, results indicated that parents hold the belief that the development of social-emotional competence and children enjoying themselves instead of academic skills is the primary purpose of preschool education. To sum up, parental play support and preschoolers’ activities at home are important predictors for children’s EF skills.